Documentary filmmakers handbook - Eckhardt, Ned, 1940- (McFarland & Co., Inc., 2012)
"A complete guide to all phases of documentary production, this is an essential handbook for student filmmakers and professional documentarians alike. Written in concise language and easy reference, the text provides a progression of real-world learning skills, including organization and design. Also itemized is the necessary equipment, with technical information for universal comprehension of equipment and application"--Provided by publisher.